A novel quantum color image steganography algorithm based on turtle shell and LSB - Wang, Meng-Xi; Yang, Hong-Mei; Jiang, Dong-Huan; Yan, Bin; Pan, Jeng-Shyang; Liu, Tao (Quantum information processing, 2022)
Quantum image steganography has attracted considerable attention in recent years. The majority of existing algorithms do not simultaneously have excellent imperceptibility, high embedding capacity, and good security. Therefore, a novel quantum color image steganography scheme is researched based on turtle shell and least significant bit (LSB) replacement. Human vision system (HVS) model and check codes are introduced into the proposed scheme to improve visual quality and security. According to the theory that HVS has different sensitivities to various colors, two channels are randomly selected with different probabilities to hide secret information from the red (R), green (G), and blue (B) channels of each color carrier pixel. Grayscale values of the two chosen channels correspond to a point in the turtle shell-based reference matrix. Depending on whether the point is at the boundary of the reference matrix or not, the LSB substitution method or turtle shell algorithm is utilized to embed the secret information. Dedicated quantum circuits are presented to better describe the procedure of the novel scheme. Experimental results show that the proposed algorithm is feasible and has superior performance in imperceptibility, embedding capacity, and security.